A century of corporate takeovers: What have we learned and where do we stand? - Martynova, Marina; Renneboog, Luc (Journal of Banking & Finance, 2008)
This paper reviews the vast academic literature on the market for corporate control. Our main focus is the cyclical wave pattern that this market exhibits. We address the following questions: Why do we observe recurring surges and downfalls in M&A activity? Why do managers herd in their takeover decisions? Is takeover activity fuelled by capital market developments? Does a transfer of control generate shareholder gains and do such gains differ across takeover waves? What caused the formation of conglomerate firms in the wave of the 1960s and their de-conglomeration in the 1980s and 1990s? And, why do we observe time- and country-clustering of hostile takeover activity? We find that the patterns of takeover activity and their profitability vary significantly across takeover waves. Despite such diversity, all waves still have some common factors: they are preceded by technological or industrial shocks, and occur in a positive economic and political environment, amidst rapid credit expansion and stock market booms. Takeovers towards the end of each wave are usually driven by non-rational, frequently self-interested managerial decision-making.